Influence of Some Dietary Organic Mineral Supplementations on Broiler Performance - Abdallah, A.G.; El-Husseiny, O.M.; Abdel-Latif, K.O. (International Journal of Poultry Science, 2009)
A trial was set up to evaluate the influence of some dietary organic mineral supplementations on broiler performance. A total of 1,500 day-old Ross 308 broiler chicks was allotted into 10 groups with 3 replicates of 50 birds each. Two control diets (negative control with inorganic minerals and positive control with organic minerals) were formulated to meet nutrient requirements of chicks recommended for Ross 308. The premix was formulated to contain the requirements of trace elements in combination of either inorganic (sulphate form) or organic form (peptide chelate form). Diets were supplemented with the organic form of zinc, copper, manganese or iron (peptide chelate at the rate of 50% or 100% of the total requirements of the elements recommended for Ross broiler chicks). Production performance was measured during the 35 day trial period and mineral excretion was evaluated at 28 day of age. Results indicated that chicks fed diets containing 100% organic minerals (Zn, Cu, Mn and Fe) had significantly higher body weight, better feed conversion, higher % tibia ash and higher immunity compared with those of inorganic control minerals treatment. Also, when organic minerals were fed as a single element while the rest of minerals were inorganic forms at a level of 100% or 50%, the performance parameters were not significantly different from those resulted from all organic minerals together but were significantly better than those of inorganic control treatment. Fecal mineral excretions from broilers receiving the organic mineral diets were lower than those of inorganic control treatment. No significant effects were observed on muscle characteristics among the different treatments. However, organic mineral diets had a positive effect on economic efficiency. It is concluded that replacing inorganic minerals with organic sources improved bird’s performance and enhanced immune response of chicks.